(untitled) (Revista Brasileira de Contabilidade e Gestão, 2018)
Innovation is mandatory today for the survival of any business. Large companies, that usually focused internally their innovation, research and development efforts, began to adopt open innovation. It is in this context, that this article seeks, through a bibliographic review, to explore the interactions that have arisen between large companies and startups. As a result of this interaction, companies benefit from agility in solving problems with lower cost and risk and startups by greater access to infrastructure, financial resources and increased market visibility. On the other hand, there are also challenges to be faced, such as discrepancy between organizational culture, intellectual property protection and asset valuation.